First insights into specificity of belowground tritrophic interactions - Rasmann, Sergio; Turlings, Ted (My University, 2008)
Tritrophic interactions involving plants, herbivores and parasites have been only recently documented for belowground systems, where entomopathogenic nematodes can exploit root herbivore induced volatile compounds to locate their hosts. Little is known, however, about whether the specificity of such interactions rivals that of the remarkable interactions found in aboveground studies. Using a belowground six-arm olfactometer that allows recording of nematode attraction, specificity of nine economically important species of different trophic levels, including plants, root feeders and entomopathogenic nematodes, was tested. We found that belowground tritrophic interactions are variable at the level of plant volatiles that are induced, elicitation by herbivores, as well as behavior of nematodes. We argue that studies on specificity and variability of belowground responses should be included in plant defense theories and in efforts to exploit tritrophic interactions to improve biological control practices.